Message piece dissemination approach for opportunistic underwater sensor network invaded by underwater spy‐robots. (22nd December 2021) - Liu, Linfeng; Zhang, Houqian; Wu, Jiagao; Xu, Jia
Abstract: Opportunistic underwater sensor network (OUSN) is deployed for various underwater applications, such as underwater creatures tracking and tactical surveillance. Particularly, the OUSN in military applications may be invaded by some underwater spy‐robots termed eavesdroppers. The eavesdroppers could move around some OUSN nodes and eavesdrop on their communication channels silently, and these eavesdropping actions are difficult to be perceived by OUSN nodes. To reduce the theft ratio of data messages and guarantee the required delivery ratio of data messages, we conceive the idea that each data message is encoded into several message pieces, and then the message pieces are disseminated to sink node individually. Besides, a lightweight encryption method is adopted to encrypt the message pieces before the dissemination. Such mechanism can protect the data messages from being stolen by eavesdroppers effectively. In this article, we propose a message piece dissemination approach (MPDA) for the OUSN invaded by some underwater spy‐robots. In MPDA, OUSN nodes disseminate the held message pieces to some selected neighboring nodes at each time slot, and a data message is considered to be delivered when all pieces of this data message have been delivered to the sink node. Extensive simulations and comparisons demonstrate the preferable performance of MPDA, that is, MPDA can reduce the theft ratio of data messages and guarantee the required delivery ratio of data messages.